Genital mycoplasma infection: a systematic review and meta-analysis - Chen Cheng; Xiangyu Chen; Yuxuan Song; Shangren Wang; Yang Pan; Shuai Niu; Rui Wang; Li Liu; Xiaoqiang Liu (Reproductive Health, 2023)
Abstract Background Recent studies have suggested that genital mycoplasma infections may be associated with male infertility. However, this association remains controversial due to time lapse, sample size, and regional prevalence. Objectives This study aimed to systematically evaluate the relationship between genital mycoplasma and male infertility through a meta-analysis and to provide a basis for the clinical management of male infertility. Methods We conducted a search on PubMed, EMBASE, the Cochrane Library, and CNKI databases, from January 2000 to June 2023 to identify case–control studies on the interrelationship between genital mycoplasma infection and male infertility. Two independent researchers performed an assessment of the methodological quality of trials according to the Newcastle–Ottawa scale and extracted data strictly based on the inclusion and exclusion criteria, and afterward, we carried out a meta-analysis using Stata 16.0. Pooled odds ratios (OR) with 95% confidence intervals (CI) were used to assess this relationship. Results This meta-analysis included 21 studies from seven countries with a total of 53025 infertility cases and 6435 controls; the age range of the participating men was from 20 to 59 years old. The results obtained showed a higher prevalence of M. genitalium, M. hominis and U. urealyticum infections in infertile men than in the controls, with the opposite result for U. parvum (M. genitalium, OR, 3.438 [95% CI: 1.780, 6.643], with P = 0.000; M. hominis, OR, 1.840 [95% CI: 1.013, 3.343], with P = 0.045; U. urealyticum, OR, 3.278 [95% CI: 2.075, 5.180], with P = 0.000; U. parvum, OR, 1.671 [95% CI: 0.947, 2.950], with P = 0.077). Further, two subgroup analyses also showed that M. hominis and U. urealyticum infections were strongly associated with male infertility in China (M. hominis, P = 0.009; U. urealyticum, P = 0.000); however, M. hominis and U. urealyticum infection was not strongly associated with male infertility worldwide (M. hominis, P = 0.553; U. urealyticum, P = 0.050). Conclusion This meta-analysis revealed that male infertility was significantly associated with M. genitalium, M. hominis and U. urealyticum infections, while U. parvum infection was not. Further, our study showed that genital mycoplasma infection influences male infertility and provides a basis for future treatment.